Arduino-based night return mechanism for passive solar trackers - Destine Mashava; Willy Stephen Tounsi Fokui (Institute of Advanced Engineering and Science, 2021)
Solar trackers are support platforms that keep photovoltaic panels facing the sun by following the sun from dusk to dawn. There exist active solar trackers that make use of motors and gears to orientate the photovoltaic panels towards the sun; and passive solar trackers that operate through the differential heating of the fluid in the tracking rack to follow the sun. Passive solar trackers suffer from the lack of a night return mechanism and a slow wake-up response in the mornings due to the limitations on the surface inclination angle of the rack. This paper seeks to address these issues by proposing an Arduino-based night return mechanism for passive solar trackers. An energy-saving heating element such as the ultra heating fabric manufactured by WireKinetics Co. is installed on the west-side canister of the tracker. Before dawn, the fabric is automatically heated and this will force the refrigerant in the west-side canister to vaporize and cool in the east-side canister, forcing the tracker to return and face eastward before sunrise. The night return mechanism is designed and simulated using proteus profesional. Simulation results show that this system can significantly optimize the function of passive solar trackers.